2020
DOI: 10.1002/jsde.12396
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature Crystallization for Separating Monoacetylated Long‐Chain Sophorolipids: Characterization of Their Surface‐Active and Antimicrobial Properties

Abstract: Pseudohyphozyma (formerly Rhodotorula) bogoriensis synthesizes long-chain-length (22-carbon chain) sophorolipids (22:0-SL) that are variously acetylated at the 6 0 -or/and 6 00 -carbons of the sophorose unit. In this paper, we describe a low-temperature crystallization protocol that preferentially separates the 6 0 -monoacetylated 22:0-SL (6 0 -Ac 1 -22:0-SL) from a parental mixture of 22:0-SL containing a majority (64.7%) of the 6 0 ,6 00diacetylated moiety (6 0 ,6 00 -Ac 2 -22:0-SL), as deduced from high-pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…P. bogoriensis produces a structurally unique sophorolipid composed of 13-hydroxydocosanoic acid ( 4 8 ), with increasing industrial applications ( 5 , 9 ). These molecules have antimicrobial properties and have been suggested as anti-inflammation and anticancer compounds ( 10 14 ). Achieving substantial improvements through genetic manipulations necessitates an understanding of the gene content.…”
Section: Announcementmentioning
confidence: 99%
“…P. bogoriensis produces a structurally unique sophorolipid composed of 13-hydroxydocosanoic acid ( 4 8 ), with increasing industrial applications ( 5 , 9 ). These molecules have antimicrobial properties and have been suggested as anti-inflammation and anticancer compounds ( 10 14 ). Achieving substantial improvements through genetic manipulations necessitates an understanding of the gene content.…”
Section: Announcementmentioning
confidence: 99%
“…The authors in that study observed antimicrobial efficiency on Propionibacterium acnes by sophorolipids embedded in different composite films such as plant-based composites pectin and alginate [ 90 ] and poly(3-hydroxybutyric acid-co-3-hydroxyvaleric acid) (PHB/HV) composites [ 91 ]. Solaiman et al [ 92 ] demonstrated that long carbon chains of acidic sophorolipids (22 carbon chains) had the strongest antibacterial effects on the tested bacteria Cutibacterium acne compared to the others including the lactonic form of sophorolipids consisting of 18 carbon chains only [ 92 ]. These results suggest that 22:0 sophorolipids are better suited biosurfactants as they possess antimicrobial properties for various applications [ 92 ].…”
Section: Applications Of Sophorolipids In Food and Healthmentioning
confidence: 99%
“…Solaiman et al [ 92 ] demonstrated that long carbon chains of acidic sophorolipids (22 carbon chains) had the strongest antibacterial effects on the tested bacteria Cutibacterium acne compared to the others including the lactonic form of sophorolipids consisting of 18 carbon chains only [ 92 ]. These results suggest that 22:0 sophorolipids are better suited biosurfactants as they possess antimicrobial properties for various applications [ 92 ].…”
Section: Applications Of Sophorolipids In Food and Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the preparation methods of SLs mainly include froth flotation, chromatography technology, crystallization at low temperature, membrane filtration, and extraction [13][14][15][16]. Among these methods, extraction technology is the most commonly used and the extractant is mainly ethyl acetate or ethanol (SLs-EAC, SLs-EtOH).…”
Section: Introductionmentioning
confidence: 99%